THE INFLUENCE OF FINANCIAL LITERACY, DIGITAL PAYMENT ADOPTION, AND PROMOTIONAL STRATEGIES ON CONSUMER PURCHASE DECISIONS THROUGH THE MEDIATION OF SHOPPING BEHAVIOR AT PT EMINA IN MALANG CITY - Early Harison Mahardhika; Ery Tri Djatmika Rudijanto Wahyu Wardhana; Agus Hermawan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Digital transformation has fundamentally altered the consumption behavior of the younger generation, particularly Generation Z, who are digital natives. In the context of the cosmetics industry, this phenomenon is evident among Emina consumers in Malang City, who exhibit high engagement with digital promotions but do not always translate this engagement into actual purchase decisions. This study aims to analyze the influence of financial literacy, digital payment adoption, and promotional strategies on consumer purchase decisions, with shopping behavior as a mediating variable, based on the Stimulus–Organism–Response (SOR) model. The research employs a quantitative approach using an explanatory research design. Data were collected through a survey of 385 Generation Z respondents who use Emina products, selected via purposive sampling. Analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine both direct and indirect relationships among the variables. The results indicate that digital payment adoption and promotional strategies have a positive and significant effect on purchase decisions, both directly and through the mediation of shopping behavior. Conversely, financial literacy does not have a significant influence, indicating the dominance of emotional and technological factors over cognitive considerations in Gen Z's consumption behavior. This study extends the SOR model by affirming the role of shopping behavior as a psychological mediator and expands the Technology Acceptance Model (TAM) into the realm of digital consumption behavior. Practically, the findings offer guidance for the cosmetics industry and fintech developers in designing more emotionally resonant, interactive, and adaptive promotional strategies and payment systems aligned with the behavior of the younger generation.